Artificial Intelligence Adoption In Higher Education In Uzbekistan: Current Trends And Future Prospects - Musurman Khurramov (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2026)
This article examines the prospects and challenges of integrating artificial intelligence (AI) technologies into the operations of higher education institutions in Uzbekistan. It analyzes both the potential benefits and the associated risks of AI adoption, drawing on the experiences of leading international universities that have successfully implemented AI-based solutions in their educational systems. Particular attention is given to the pedagogical application of the ChatGPT platform in teaching and learning processes. In addition, the study identifies a set of priority measures that higher education institutions should undertake to ensure the effective and responsible deployment of AI technologies. The article also explores practical approaches for maximizing the educational, administrative, and analytical potential of AI platforms within the higher education system.